2007
DOI: 10.4000/asp.483
|View full text |Cite
|
Sign up to set email alerts
|

Language learning as discourse analysis: Implications for the LSP learning environment

Abstract: Au cours de la deuxième moitié du vingtième siècle, l’enseignement des langues de spécialité a été fortement influencé par l’approche communicative et par la recherche en analyse du discours, surtout dans le domaine du genre. L’intégration de la recherche en linguistique de corpus dans l’apprentissage des langues est un phénomène plus récent. À partir de 1990 les publications sur l’emploi des concordances par les professeurs et les apprenants de langues se sont multipliées. Le but de cette étude est de rapproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…As he remarked, “experience in using concordance data reactively has indicated that it could be used proactively also in a more traditional teacher‐centered setting, and has suggested also a range of concordance‐based exercise types” (Johns, 1991a, p. 31). Although there have been only occasional attempts by others to promote prepared concordance printouts from publicly available resources (e.g., Chambers, 2007a; Chambers & Kelly, 2004), the consensus seems to be that paper‐based materials are not in themselves incompatible with DDL (e.g., Breyer, 2006; Frankenberg‐Garcia, 2005a).…”
Section: Paper‐based Materials In Ddlmentioning
confidence: 99%
See 2 more Smart Citations
“…As he remarked, “experience in using concordance data reactively has indicated that it could be used proactively also in a more traditional teacher‐centered setting, and has suggested also a range of concordance‐based exercise types” (Johns, 1991a, p. 31). Although there have been only occasional attempts by others to promote prepared concordance printouts from publicly available resources (e.g., Chambers, 2007a; Chambers & Kelly, 2004), the consensus seems to be that paper‐based materials are not in themselves incompatible with DDL (e.g., Breyer, 2006; Frankenberg‐Garcia, 2005a).…”
Section: Paper‐based Materials In Ddlmentioning
confidence: 99%
“…As he remarked, "experience in using concordance data reactively has indicated that it could be used proactively also in a more traditional teachercentered setting, and has suggested also a range of concordance-based exercise types" (Johns, 1991a, p. 31). Although there have been only occasional attempts by others to promote prepared concordance printouts from publicly available resources (e.g., Chambers, 2007a;Chambers & Kelly, 2004), the consensus seems to be that paper-based materials are not in themselves incompatible with DDL (e.g., Breyer, 2006;Frankenberg-Garcia, 2005a). This is not to deny that direct consultation is essential if learners are to benefit fully and autonomously from the possibilities that corpora have to offer, but at the same time there seems to be no reason to rule out more teacheroriented applications in earlier stages:…”
Section: Advantages and Limitations Of Paper-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of accurate pre-SIM astrometry, we note that large-scale ground-based photometric surveys such as Pan-STARRs will also provide astrometry at the required (sub-mas) level (Chambers 2005). Also, data from the Gaia mission (Perryman 2002) will help explore and characterize SSGAs more fully.…”
Section: Very Long-period Companionsmentioning
confidence: 99%
“…The density of air fluctuates with barometric pressure and temperature, and the concentrations of water vapour and other atmospheric constituents such as aerosols (see, e.g. Chambers 2005, and references therein). To first order, however, airmass will increase linearly with barometric pressure p and relative humdity ρ, Z = pρ/(pρ).…”
Section: Introductionmentioning
confidence: 99%